Annular flow enhanced two-phase evaporative heat exchanger for space-based systems - Nikanpour, D. (Cranfield University, 1991)
The development of multi-kilowatt space-based systems requires the transport of waste heat loads over long distances in micro-gravity conditions. In this context two-phase heat transport systems are attractive enabling a high rate of heat transport with low pump powers compared to single phase systems. In this context the design of a two-phase heat exchanger to transfer heat from a single-phase fluid (water) to a two-phase fluid (Freon 114) is discussed. Until reliable micro-gravity (< 10-3g) test data on the heat transfer and pressure drop in a two-phase flows are available, it is deemed necessary that the design of heat exchangers' passages should promote gravity-independent flow regimes. This would make the design and test data, obtained at ground conditions, applicable in micro-gravity environments. The design concept investigated hinges on utilising a set of helical flow passages (with small cross sectional area) to ensure a predictable flow regime, annular flow, up to high vapour qualities (>0.8), in both micro-gravity and one Ig' environments. The concept was applied to the design of a 5kW helically coiled evaporative heat exchanger for space-based systems, which was subsequently manufactured and tested. Ground tests gave results close to analytical predictions based on computer simulations of the heat transfer and pressure drops in helical flow passages. Finally design guideline for a two-phase evaporative heat exchanger for space-based systems is provided, along with . conclusions and areas to be further researched.